Visual stratigraphy linescanner images from the Alpine ice core KCC (2013) - Kipfstuhl, Joseph; Hoffmann, Helene; Kerch, Johanna; Binder, Tobias; Erhardt, Tobias; Bohleber, Pascal (PANGAEA - Publishing Network for Geoscientific and Environmental Data, 2018)
Kipfstuhl, Sepp; Hoffmann, Helene; Kerch, Johanna; Binder, Tobias; Erhardt, Tobias; Bohleber, Pascal (2018): Visual stratigraphy linescanner images from the Alpine ice core KCC (2013). Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research, Bremerhaven, PANGAEA, https://doi.org/10.1594/PANGAEA.887684, In supplement to: Kerch, Johanna; Eisen, Olaf; Binder, Tobias; Freitag, Johannes; Bohleber, Pascal; Bons, Paul D; Weikusat, Ilka (in review): Short-scale variations in high-resolution crystal-preferred orientation data in an alpine ice core - do we need a new statistical approach? Journal of Geophysical Research-Earth Surface